2020
DOI: 10.1002/joc.6778
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐day variability of temperature and its near‐surface gradient with elevation over mountainous terrain: Comparing MODIS land surface temperature data with coarse and fine scale near‐surface measurements

Abstract: Where land surface air temperature data are not available, satellite land surface temperature are used. However, the coarse spatial resolution of satellitederived products may yield errors at the local scale. This work shows the differences between the MODIS Land Surface Temperature and Emissivity (MOD11A1) product and ground measurements at two different scales. We used data from 21 SNOTEL stations across the northern Front Range of Colorado to represent the coarse scale and 17 iButton temperature sensors acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Conversely, despite the good correlation of air temperature with LST (R 2 of 0.80), they are different variables and LST should not be used directly to characterize air temperature patterns. The comparison between the different estimations of air temperature with LST showed considerable biases, as previously observed [8]. For the best estimation of air temperature in this study (merged KED), 73% of the MODIS pixels showed a value of LST within the stated uncertainty range (from estimate −σ to estimate + σ).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Conversely, despite the good correlation of air temperature with LST (R 2 of 0.80), they are different variables and LST should not be used directly to characterize air temperature patterns. The comparison between the different estimations of air temperature with LST showed considerable biases, as previously observed [8]. For the best estimation of air temperature in this study (merged KED), 73% of the MODIS pixels showed a value of LST within the stated uncertainty range (from estimate −σ to estimate + σ).…”
Section: Discussionsupporting
confidence: 79%
“…SNOTEL temperature decreases with elevation but the correlation between both variables is moderate; the R 2 of the linear relationship is 0.21 for the whole domain and 0.50 for the estimation area (see Figure 3a). Similar results were found for this study area in a previous analysis [8]. The scarce air temperature data from SNOTEL were complemented by well-sampled secondary information from elevation and LST in order to obtain air temperature fields.…”
Section: Analysis Of the Secondary Informationsupporting
confidence: 86%
See 3 more Smart Citations